Overview of Vehicle-to-Everything Communication: Technological Advancements, Applications, and Future Prospects in Intelligent Transportation Systems - Bintoro, Ketut Bayu Yogha (JISA(Jurnal Informatika dan Sains), 2025)
Vehicle-to-Everything (V2X) communication is a cornerstone technology in modern Intelligent Transportation Systems (ITS), enabling real-time data exchange between vehicles, infrastructure, pedestrians, and networks. V2X enhances road safety, traffic management, and driving experience, contributing to the global vision of connected and autonomous transportation. This paper presents a comprehensive overview of V2X communication, detailing its key components, types, and technological standards, including Dedicated Short-Range Communication (DSRC), LTE-V2X, and 5G. We explore current applications of V2X, such as safety enhancements, traffic optimization, infotainment, and environmental sustainability, and discuss significant challenges in deployment, including technical limitations, security and privacy concerns, and infrastructure requirements. Furthermore, this study examines future directions in V2X, emphasizing the role of 5G, edge computing, AI integration, and the implications for electric and autonomous vehicles. Realizing V2X's full potential requires robust policy support, international standardization, and infrastructure investments, particularly in countries with varying levels of technological maturity. This paper provides insights into the evolution of V2X and outlines critical considerations for advancing toward a safer, more efficient, and sustainable global transportation ecosystem